Data Science for Internal Audit in Banking: Refinement of an Internal Audit Alarmistic System with Machine Learning - Crisóstomo, Laura Inês Bleeker Casquinha (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science